The Determinants of Undiagnosed Hypertension Among Indonesian Adults: A Cross-sectional Study Based on the 2014-2015 Indonesia Family Life Survey - Yeni Mahwati; Dieta Nurrika; Kamaluddin Latief (Korean Society for Preventive Medicine, 2022)
Objectives This study investigated the determinants of undiagnosed hypertension among Indonesian adults. Methods This study involved an analysis of secondary data from the 2014 Indonesia Family Life Survey (IFLS) on 5914 Indonesian adults (≥40 years). The determinant variables examined in this cross-sectional study were education level, monthly per capita expenditures (PCE), whether the participant experienced headaches in the morning, and other general health variables. The outcome variable was undiagnosed hypertension, which was defined as participants with hypertension who had not received a hypertension diagnosis from a health professional and had never been prescribed medication for treating hypertension. The data were analyzed using logistic regression. Results A total of 3322 participants (56.2%) were found to have undiagnosed hypertension. The odds ratios (ORs) and 95% confidence intervals (CIs) of undiagnosed hypertension were significantly higher among those who completed primary school or lower (OR, 1.60; 95% CI, 1.29 to 1.98), had low monthly PCE (OR, 1.28; 95% CI, 1.13 to 1.43), did not report experiencing headaches in the morning (OR, 1.97; 95% CI, 1.76 to 2.21), and reported a general health status of healthy (OR, 2.05; 95% CI, 1.82 to 2.30) than those who had a higher education level, had high monthly PCE, experienced headaches in the morning, and were unhealthy. Conclusions Education level, monthly PCE, the experience of headaches in the morning, and general health status were associated with undiagnosed hypertension. The monitoring system for detecting undiagnosed hypertension cases must be strengthened. Health promotion is also necessary to reduce the prevalence of undiagnosed hypertension.